How Does AR Technology Adoption and Involvement Behavior Affect Overseas Residents’ Life Satisfaction? - Nargis Dewan; Md Billal Hossain; Gwi-Gon Kim; Anna Dunay; Csaba Bálint Illés (Big Data and Cognitive Computing, 2022)
This study aims to better understand foreign residents’ life satisfaction by exploring residents’ AR technology adoption behavior (a combination of transportation applications’ usefulness and ease of use) and travel involvement. Data were collected from 400 respondents randomly through a questionnaire-based survey. SPSS and AMOS were used to analyze and gather results. This study suggests overall life satisfaction as an operationalized dependent variable to measure a traveler’s sense of satisfaction, a traveler’s involvement, and AR adoption of necessary transportation apps is constructed as an independent variable. The model was proposed to explore the impacts of travel satisfaction on overall life satisfaction. The model focused on the role of traveling involvement when it is considered a first variable to explore the impact of travel satisfaction on the overall quality of life. Furthermore, AR technology adoption behavior is where people use traveling apps before and during traveling to fulfill travel needs, obtain details about locations, and make proper arrangements, as well as other facilities. Two significant roles of transportation apps and travelers’ involvement in travel-satisfaction development and overall life satisfaction were found; variables had a positive effect on travel satisfaction and life satisfaction. The results also revealed that AR mobile travel applications with traveler involvement could help improve individual overseas residents’ travel satisfaction; travel satisfaction provides more feelings of satisfaction with life in South Korea.